Ventilated cavity flows behind a backward facing step with a combination computational fluid dynamics and Error Back Propagation algorithm - He, Zanyang; Sun, Tiezhi; Zou, Li; Jiang, Yichen; Duan, Lei (Ocean engineering, 2022)
Ventilated cavity flow is of a great practical interest for the features that may reduce the drag around the area near the cavity. The present paper demonstrates the prediction of ventilated cavity flows on the backward facing step, which establishes the prediction model of drag reduction by the numerical simulation and artificial intelligence algorithm. The results of the computational fluid dynamics are compared with available experimental data to validate the precision, which shows good agreement. This paper numerically analyzes the influence of the number, location and part ventilation volume of injectors on the drag reduction of ventilated cavity flows. With the same air-entrant coefficient, the number and location of injectors both have a significant impact on drag reduction performance. And the part ventilation volume of the injectors may also have a limited impact. Accordingly, the prediction model of drag reduction is established by the Error Back Propagation algorithm (BP algorithm) that has accurate algorithms and fast calculation to save time and computing resources. Meanwhile, the results indicate that BP algorithm can reasonably predict the performance of ventilated cavity flows, which means the model can optimize the drag reduction on ventilated cavity flows and it can be useful in engineering. •The effect of injectors on the drag reduction performance of ventilated cavity flows are investigated.•The influence of the injector location on the drag reduction performance are evaluated.•An optimization study is carried out based on the Error Back Propagation algorithm for ventilated cavity flows.